MEDIA SOSIAL DAN PEMBENTUKAN IDENTITAS BUDAYA REMAJA: PERSPEKTIF KONSELING MULTIKULTURAL DI ERA DIGITAL - Mey Wahyu Nur Hidayah; Fiisabilillah Jannah; Maulidia Aulia; Naura Aisya Maghfiradina; Anita Dhuwi Rahayu; Ari Khusumadewi; Ela Nur Fadilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of social media in shaping the cultural identity of young people in the digital age through the perspective of multicultural counseling. The method used is a literature review with a qualitative approach using relevant academic sources. The findings indicate that social media has become a primary platform for identity formation through online interactions and exposure to global culture, which has led to cultural hybridization between local and global values. The impact is dual: expanding modes of expression while also potentially causing an identity crisis and diminishing the strength of local culture. Therefore, multicultural counseling is essential to support young people  integrating their identities in a balanced manner amidst digital developments.